Mechanical and laser drilling of thick carbon fibre reinforced polymer composites (CFRP) - Sharizal Ahmad Sobri (2017)
Carbon fibre reinforced polymer, or CFRP composite materials, play an increasingly important role in modern manufacturing. They are widely used in aerospace, and their use is currently Spreading to other industries where high strength-to-weight ratios are required. However, machining of composites is still a challenging task and often hampered by poor quality. Despite the extensive research that was conducted on the machining of composite materials over the last few years, mechanical drilling still suffers from delamination, fibre pull-out and poor surtace finish, whereas laser cutting produces microstructured defects and a taper problem. This thesis reports on the drilling of CFRP composites by demonstrating the possibility of drilling small diameter holes (i.e. 8mm) into 25.4mm thick carbon fibre reinforced polymer composites (CFRPs) using mechanical drilling and laser drilling as stand-alone processes and as a sequential combination. The research involved four main phases of experimental testing. The first part of Phase 1 involved preliminary experiments of drilling thick CFRP to identify the most suitable drilling strategy. Three mechanical drilling strategies conducted in the same parameter by using a 2-flute uncoated WC twist drill that was assessed with respect to feasibility of drilling thick CFRP. The results showed that the single-step strategy was the most feasible strategy to drill thick CFRP compared to 2- and 4-peck drilling strategies. The second part of Phase I concerned the influence of speed-feed co nations on hole quality by utilising three twist drills with different materials and geometries in both an uncoated and coated condition. The results indicated that a significant increase in peel-up delamination was found with increasing feed rate. In contrast, using a constant feed rate but increasing the spindle speed seemed to reduce peel-up delamination. Furthermore, the hole entry for 2-flute uncoated WC drill bits was an uncommon study finding because most of the previous researchers experienced more damages at the hole exit and their investigation focused on the hole exit only. Currently, implementation of laser technology in cutting and drilling composites is becoming popular as an altenative solution. Various experiments were conducted with the goal of identifying the effects of machining parameters on key output measures (i.e. heat affected zone(HAZ), hole depth and other damages) in drilling of 25.4 mm thick CFRP by using a fibre laser. Phase 2 involved a number of machining parameters selected to identify the potential of a fibre laser in drilling thick CFRP composites (i.e. laser power, scanning speed, focal point plane position (FPP), assisted-gas type and gas pressure). The results proved that a fibre laser could penetrate thick CFRP to a 22mm depth only. Moreover, the spiral trepanning strategy was able to penetrate 80% out of the total thickness of the CFRP in continuous wave (CW) mode, whereas the modulated laser beam (i.e. laser pulse mode) can penetrate 67% only. This result was a major recorded breakthrough because previous research attempts cut up to Smm only. Laser power proved to be the most influential factor for hole depth in laser drilling of thick CFRP when the spiral trepanning strategy was applied. Machining rials were conducted in Phase 3 by using a 16kW fibre laser in modulated pulsed laser mode. In this phase, laser power of more than 1kW was attempted to cut the whole thickness of CFRP composites in CW mode, but it was unsuccessful. However, a new parameter was discovered (i.e. the cooling time between passes in modulated pulsed mode), which proved a considerable reduction of HAZ when the higher cooling time was imposed. Finally, phase 4 involved the experiments of sequential laser-mechanical drilling. A 1kW fibre laser was selected as a pre-drilling or initial step and followed by mechanical drilling as the final step. The sequential drilling method successfully reduced thrust force and torque for mechanical drilling by an overall average of 61%, resulting in high productivity and decreasing the thermal and mechanical stresses in the cutting tool and, in turn, promoting higher tool life. The highest delamination factor (Fa) ratio was experienced by the sequential laser 8mm - mechanical 8mm for both tools (i.e. 2- and 3-flute uncoated tungsten carbide) and laser pre-drilling strategies (i.e. single- and double-side). Thus, a novel laser-mechanical sequential drilling technique was developed, evaluated and tested in the drilling of thick CFRP composites; this is the first time ever in drilling thick CFRP (i.e. 25.4mm).